2017
DOI: 10.1155/2017/9026219
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoparticles as a Redispersing Additive in Magnetorheological Fluid

Abstract: Unwanted agglomeration of micro particles in magnetorheological fluid is an important problem for many technological applications. Furthermore, the stability of this kind of fluid is also studied as an important property in many research papers. Prior to use, a redispersion of agglomerated or aggregated (connected by solid phase) particles is often necessary. The objective of this study is to evaluate the dispersibility effect of magnetic nanoparticles as a carrier, while keeping the magnetorheological (MR) ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In spite of the certainly wide variety of magnetic nanoparticles (MNPs) with different geometries, compositions and functionalizations [1,2,3,4,5,6,7,8] that have become available in recent years, and of the number of applications that have been devised for them [1,9,10,11,12], when the goal is to provide a nanocarrier suitable for targeted chemotherapy, there is still room for progress. On one hand, the methods for obtaining MNPs need to be more cost- and time-effective, eco-friendly, and scalable.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the certainly wide variety of magnetic nanoparticles (MNPs) with different geometries, compositions and functionalizations [1,2,3,4,5,6,7,8] that have become available in recent years, and of the number of applications that have been devised for them [1,9,10,11,12], when the goal is to provide a nanocarrier suitable for targeted chemotherapy, there is still room for progress. On one hand, the methods for obtaining MNPs need to be more cost- and time-effective, eco-friendly, and scalable.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if the settled particles are redispersed at a reasonably low shear rate, then the use of such MR fluid can be justified for a particular application, though it gets settled. Iglesias et al, [ 26 ] Portillo et al, [ 27 ] and Martin et al [ 20 ] have used ASTM‐D5‐05a method, while López‐López et al, [ 25 ] Leong et al, [ 19 ] and Niu et al [ 21 ] have demonstrated the use of rheometer for characterization of redispersion. The methods proposed so far are indirect, while we are proposing a slider crank mechanism based setup for shearing (redispersing) the settled sample at a given shear rate.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…López‐López et al [ 25 ] and Leong et al [ 19 ] compared the redispersion behavior of MR fluid with different surfactants (oleic acid, aluminum stearate, and silica nanoparticles—Aerosil 300). In a similar line, Iglesias et al, [ 26 ] Portillo and Iglesias, [ 27 ] and Martin et al [ 20 ] have used penetration standard needle (ASTM‐D5‐05a) for the characterization of the redispersibility of different MR fluids. The stiffness of the sediments was measured to characterize the redispersion in their study.…”
Section: Introductionmentioning
confidence: 99%
“…bidisperse Mn–Zn ferrite spherical particle) form a single chain, and consequently, the fluid has less strength. High concentrations of magnetic particles lead to the formation of stronger and thicker chains, resulting in larger yield strength (Portillo and Iglesias, 2017). Moreover, Kumar et al (2019) it has been experimentally shown that the addition of magnetic nanoparticles increases the yield strength, while nanoparticles occupy voids between the microparticles and form regular chains when the external magnetic field is applied.…”
Section: Stabilization and Tribological Propertiesmentioning
confidence: 99%
“…Moreover, Kumar et al (2019) it has been experimentally shown that the addition of magnetic nanoparticles increases the yield strength, while nanoparticles occupy voids between the microparticles and form regular chains when the external magnetic field is applied. It turned also out that shear stress is greater in the case of MRF with magnetic nanoparticles included (Portillo and Iglesias, 2017). According to the superparamagnetic-based MRF, Brownian motion influences the particles much less than the interactions between particles and with the external magnetic field.…”
Section: Stabilization and Tribological Propertiesmentioning
confidence: 99%